2021
DOI: 10.3389/fpsyt.2021.713210
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Alexithymia, Social Support, and Duration of Methamphetamine Use Among Male Methamphetamine-Dependent Patients

Abstract: Introduction: China has 1.18 million methamphetamine abusers. Among the illegal drugs in China, methamphetamine has the highest abuse rate. Although previous studies have indicated a positive relationship between alexithymia and declining social support, the incidence of alexithymia, the total duration of methamphetamine dependence, social support, and the relationships between them among methamphetamine-dependent patients in the Chinese population have been rarely reported.Methods: A total of 113 methamphetam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…We found that metropolitan residential area was unrelated to social support-a finding that agrees with the literature (Jalali et al, 2019). Methamphetamine dependence, duration of methamphetamine use, and anxiety were not independently associated with social support in our study, but were in broadly relevant past studies (Cui et al, 2021;Lanyon et al, 2019;Semple et al, 2011). The residential area, methamphetamine dependence, duration of methamphetamine use, and anxiety variables in our study were, however, associated with social support in univariable analyses.…”
Section: Discussionsupporting
confidence: 89%
“…We found that metropolitan residential area was unrelated to social support-a finding that agrees with the literature (Jalali et al, 2019). Methamphetamine dependence, duration of methamphetamine use, and anxiety were not independently associated with social support in our study, but were in broadly relevant past studies (Cui et al, 2021;Lanyon et al, 2019;Semple et al, 2011). The residential area, methamphetamine dependence, duration of methamphetamine use, and anxiety variables in our study were, however, associated with social support in univariable analyses.…”
Section: Discussionsupporting
confidence: 89%
“…Secondly,this study only includes two representative factors in the benefits and barrierse model. In future research, we shoul choose more factors to include in the study, such as alexithymia as benefit for the incidence of alexithymia is significantly higher in MA addicts than in the general population [39], and the reason why many people hurt themselves is to establish communication with others [22]. Finally, though eforts were made to control confounding variables, other key variables such as whether they got enough self-control may also had an impact on predicting aggresion towards themself, as study have shown [40].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown a strong relationship between alexithymia and addiction, such as heroin addiction (Psederska et al, 2019), alcohol addiction (Thorberg et al, 2019), internet addiction (Mahapatra & Sharma, 2018), and pathological gambling (Marchetti et al, 2019). Cui et al (2021) found that the prevalence of alexithymia in MUD patients was 23% compared to 16.67% in the healthy controls. Long-term MA use led to increased di culty in identifying emotions in patients, but the duration of MA use was not related to the dimensions of di culty describing feelings (DDF) and externally oriented thinking (EOT).…”
Section: Introductionmentioning
confidence: 90%
“…People with alexithymia lack imagination and empathy, so they have poor comprehension of mood changes (Mahapatra & Sharma, 2018). In turn, di culties in identifying emotions are associated with MA use and relapse (Cui et al, 2021). Numerous studies have shown a strong relationship between alexithymia and addiction, such as heroin addiction (Psederska et al, 2019), alcohol addiction (Thorberg et al, 2019), internet addiction (Mahapatra & Sharma, 2018), and pathological gambling (Marchetti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%